From Genetics to Epigenetics, Roles of Epigenetics in Inflammatory Bowel Disease - Zeng, Zhen; Mukherjee, Arjudeb; Zhang, Hu (Frontiers in Genetics, 2019)
Inflammatory bowel disease (IBD) is a destructive, recurrent, and heterogeneous disease. Its detailed pathogenesis is still unclear, although available evidence supports that IBD is caused by a complex interplay between genetic predispositions, environmental factors, and aberrant immune responses. Recent breakthroughs with regard to its genetics have offered valuable insights into the sophisticated genetic basis, but the identified genetic factors only explain a small part of overall disease variance. It is becoming increasingly apparent that epigenetic factors can mediate the interaction between genetics and environment, and play a fundamental role in the pathogenesis of IBD. This review outlines recent genetic and epigenetic discoveries in IBD, with a focus on the roles of epigenetics in disease susceptibility, activity, behavior and colorectal cancer (CRC), and their potential translational applications.